Interactive effects of temperature and metal toxicity on Scenedesmus quadricauda and Chlamydomonas augustae / Yong Wai Kuan - Yong , Wai Kuan (2019)
Abiotic stresses have significant implications on the growth of aquatic organisms, including microalgae which are the primary producers of the food chain. Heavy metals (HMs) such as copper (Cu) and nickel (Ni) are essential trace nutrients involved in the electron transfer, redox reaction, signalling mechanisms, and oxidative stress response of microalgae. However, when present at high concentrations, HMs are known to induce toxic effects on chlorophyll synthesis, photosynthetic efficiency, growth, reactive oxygen species (ROS) generation, and cellular metabolism. Heavy metal speciation and distribution in the aquatic environment is dependent on water temperature, which is a key environmental factor that strongly regulates growth of photosynthetic organisms. To date, inhibitory mechanism of heavy metals on microalgae at metabolic level, and its integrative effects with rising water temperature, remain unclear. In this study, the interactive effects of temperature and metal toxicity on two freshwater green microalgae, Scenedesmus quadricauda and Chlamydomonas augustae, were elucidated from the physiological (growth, photosynthesis, ROS, metal uptake) and biochemical (metabolite) aspects. Cell density of both species decreased with increasing concentrations of Cu and Ni. Photosynthetic parameters of the two microalgae obtained from the pulse amplitude modulated (PAM) fluorometry demonstrated that the maximum relative electron transport rate (rETRm), light harvesting efficiency (?), saturation irradiance of electron transport (Ek) and non-photochemical quenching (NPQ) were sensitive to both stressors. The increased level of ROS corresponded to the increasing concentrations of HMs. Both species were able to accumulate substantial amount of Cu and Ni in their biomass. Untargeted mass-spectrometry metabolite profiling was used to understand the changes in metabolic flux and biochemical pathways. In general, the two species underwent primary metabolism restructuring for adaptation and restoration of homeostasis. The results show that amino acids, fatty acids and sugars were the key primary metabolites involved in the microalgal adaptation. Amino acids and proteins were involved in chelating metal ions and reducing free metal ions in the cells. Pathways related to the carbohydrate and energy metabolism were also involved in the response, suggesting a change in energy expenditure. Sulfur-containing metabolites and sulfur metabolism were also significantly dysregulated because excess metal ions would bind to various ligands. Overall, S. quadricauda was more resistant to heat and metal toxicity than C. augustae, suggesting that S. quadricauda is a better candidate for phycoremediation. By integrating results from the physiological and biochemical responses, this project provides insights into the underlying mechanisms of the interactive stress response in green microalgae from the aquatic environment. Global warming and aquatic toxicology have been closely associated with microalgal metabolism, species abundance and diversity. Understanding the interactive effects of multiple stressors is crucial to predict microalgal responses to environmental changes which might affect community tolerance and species distribution in the long run.